1994
DOI: 10.1161/01.str.25.11.2126
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in severity of cerebrovascular events.

Abstract: Background and Purpose This study was conducted to determine if blacks hospitalized for cerebrovascular events had more severe cerebrovascular events than whites similarly hospitalized.Methods Data from the Maryland Health Services Cost Review Commission were used to determine incidence of coma, death rates, age at death of those who died, and length of stay for acute hemorrhagic and occlusive stroke in hospitalized blacks and whites after adjusting for sex and, if appropriate, age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 30 publications
3
32
3
Order By: Relevance
“…In multivariable analyses adjusting for ICH risk factors, NHPI race was an independent predictor of young ICH. The age disparity seen in our study is similar to the age disparities reported in other ICH observational studies comparing non-Hispanic white subjects to Maoris from New Zealand, 20 Mexican Americans, 21 and black patients 22,23 with ICH, and supports the idea that minority racial groups have a significantly younger age at presentation with ICH. Since NHPI have been historically grouped with Asians into a single racial category in many studies, prior ICH studies may have masked substantial differences in disease characteristics and outcomes among the NHPI group.…”
Section: Discussionsupporting
confidence: 89%
“…In multivariable analyses adjusting for ICH risk factors, NHPI race was an independent predictor of young ICH. The age disparity seen in our study is similar to the age disparities reported in other ICH observational studies comparing non-Hispanic white subjects to Maoris from New Zealand, 20 Mexican Americans, 21 and black patients 22,23 with ICH, and supports the idea that minority racial groups have a significantly younger age at presentation with ICH. Since NHPI have been historically grouped with Asians into a single racial category in many studies, prior ICH studies may have masked substantial differences in disease characteristics and outcomes among the NHPI group.…”
Section: Discussionsupporting
confidence: 89%
“…This may be driven by a disproportionate number of severe strokes from minority patients within these hospitals. 22,23 However, our findings demonstrate that increased risks associated with these hospitals affect all racial and ethnic groups. For example, white patients treated in hospitals with the highest black/Hispanic admission rates have a 2% absolute increase in the adjusted probability of feeding tube placement compared to those treated in hospitals with the lowest rates.…”
mentioning
confidence: 57%
“…These findings may be at least partly driven by greater stroke severity 22,23 and a greater number of clinically eligible minority patients. However, these differences may also result from diversity in preferences or disparities in how providers and institutions interpret these preferences.…”
mentioning
confidence: 99%
“…41 Evidence from US-based studies reveals a direct relationship between stroke severity and other contributory factors such as in-hospital mortality, duration of stay, poor Glasgow Coma Scale score, and incontinence during acute presentation. 42 Although the Leicestershire Stroke Study reported a significant association between development of incontinence during the acute stage and 28-day stroke morbidity in South Asians, there is limited information on the impact of South Asian ethnicity on stroke severity. …”
Section: Predictors Of Stroke Severity In South Asiansmentioning
confidence: 99%